Non-Linear Derivative Interactions in Relativistic Hadrodynamics - Gaitanos, T.; Kaskulov, M. (HNPS Advances in Nuclear Physics, 2019)
The Lagrangian of Relativistic Hadrodynamics (RHD) is extended by introducing non-linear derivative (NLD) operators into the interactions between the nucleon with the meson elds. As the novel feature of the NLD model, the nucleon selfenergy depends on both, on energy and density. Our approach contains a single cut-o parameter, which determines the density dependence of the nuclear equation of state (EoS) and the energy dependence of the nucleon-nucleus optical potential. The NLD formalism is compatible with results from microscopic nuclear matter calculations as well as with Dirac phenomenology.